Financially focused project management - Cappels, Thomas M. (Boca Raton, FL : J. Ross Pub., 2004)
The book supplies a wide range of strategies and methods to help you successfully meet the challenges of changing economic conditions, technology, resources, requirements, schedules, and budgets. Written by a best-selling author and expert with over 20 years of experience, this financially focused book contains project management methods that you can use to ensure your company successfully meets established consumer and shareholder expectations and investment community demands. Cappels$1 (Bclear and concise explanations of proven financially focused project management tools and techniques, including the human aspects, give you a varied and flexible skill set.s
Includes bibliographical references and index.
oif 10/10/14; rua 23/02/15
Loans
Keywords: Project management; Project management - finance; Project management - cost effectiveness